Evaluación electromiográfica de la actividad del músculo masetero en masticación en pacientes con neutroclusión, mesoclusión y distoclusión. (2022)
A clinical examination, cephalometric analysis and electromyographic examination were performed in 35 patients between the ages of 13 and 56 years. The volunteers were classified on their skeletal classifications in three groups: Normocclusion (Class I), distocclusion (Class II) and mesocclusion (Class III). EMG recordings were obtained with a repetition of chewing with pink wax, taking first the right masseter followed by the left masseter. Initially, the type of distribution of the electromyographic data was verified using the ShapiroWilks test, the distribution is acceptably normal for all variables except the minimum electrical activity value. The SPSS 26.0 program was used and the significance level was set at p = 0.05.